Angry like Jesus : using His example to spark your moral courage - Sumner, Sarah (Fortress, 2015)
The Gospels include at least fifteen different stories about Jesus' anger. Jesus' anger shows us what godly anger is. Although sinful anger cannot achieve the righteousness of God, godly anger can rouse a sleeping church. Godly anger stirs people to wake up and be truthful so that many can be healed. Godly anger is the antidote to arrogance and addictions and senseless violence. It's the cure for selfish fearfulness and complacency. It's the spark for moral courage. It's the match that lights new fire for renewal in the church.